The Influence of Video Modeling on Mother's Ability in Readiness to Implement Toilet Training in Toddler Age - Indra Rahmad; Julhana Julhana; Heni Nurhaeni (International Journal of Social Service and Research, 2023)
Toddler age (1-3 years) is the golden age because children at This age experience very rapid growth and development. One of the developmental tasks during toddlerhood is toilet training (Khaironi, 2018). Defecation or urination training for children really requires preparation for the mother, both physically, psychologically and intellectually. Quantitative research with a quasi-experimental approach with control group design. Pre-test and post-test control group research design. The sampling technique was purposive sampling involving 100 respondents. The results of data analysis using the Wilcoxone test showed a p-value of 0.000 (p<0.05) for the variables knowledge, attitude, mother's actions, and child's abilities. Before or after being given intervention in the experimental group using video modeling. These results show that Ha is accepted and H0 is rejected so it can be interpreted that there is an influence of providing video modeling on mother's knowledge, attitudes, actions, and child's abilities in the mother's readiness carry out toilet training at toddler age. Statistical test results in the control group shows a value of 0.002 (p<0.05) at knowledge variable which means the toilet training ability value In the control group there was an increase before and after administration intervention. Then on the variables of attitude, mother's actions, and child's abilities obtained was 0.001 (p<0.05). This means that there was an increase before and after the intervention was given the control group used the booklet.